Rifted Margins: State of the Art and Future Challenges - Peron-Pinvidic, Gwenn; Manatschal, Gianreto; , the “IMAGinING RIFTING” Workshop Participants (Frontiers in Earth Science, 2019)
Improvements in seismic imaging, computing capabilities and analytical methods, as well as a number of industry deep-water wells sampling distal offshore settings, have underpinned new concepts for rifted margin evolution developed in the last two decades; these mark significant progress in our understanding of extensional systems. For example, the tectonic, sedimentary and magmatic processes linked to the formation of rifted margins have been overhauled, giving rise to more quantitative approaches and new concepts. However, these processes cannot be understood in isolation, requiring consideration of the continuum in which inheritance and physical processes are integrated within a plate tectonic framework. The major progress and fundamental developments of past research in rifted margins have been made hand-in-hand with other domains of Earth Sciences and have fundamental implications for the understanding of key geological systems such as active rifts, the ocean lithosphere, subduction zones, and collisional orogens. The 'IMAGinING RIFTING' workshop, organized in Pontresina-Switzerland in September 2017, gathered researchers from all disciplines working on rifts and rifted margins, and included participants from academia and industry. This contribution summarizes the workshop discussions, in addition to outlining our state-of-the-art knowledge of rifted margins. We highlight future challenges in unravelling the processes and conditions under which these extensional systems form and, ultimately, how tectonic plates rupture and new oceans are born. Our aims here are to provide a framework for future research endeavours and to promote collaboration not only within the rift and rifted margins communities, but across other Earth Science disciplines.